Teachers and Tests Changes in the New York State Testing Program - S. G. Grant (Arizona State University, 2000)
How do teachers change their pedagogical practices? While many current initiatives seek to raise educational standards and improve student academic performance, there is a curious gap in national and state reforms. Considerable attention is given to defining higher expectations for what students will know and be able to do, yet little attention is given to how teachers should learn new pedagogical ideas and practices. This exploratory study uses focus group interview data collected over two years to examine how cross-subject matter groups of elementary and secondary New York State teachers respond to one way of learning to change their classroom practices: state-level testing. Analysis of the data highlights three issues: the nature and substance of the tests, the professional development opportunities available to teachers, and the rationales for and consequences of the state exams.